Identification of optimal investments - Lividini, Keith; Fiedler, John L.; Zeller, Manfred; Asare-Marfo, Dorene; Funes, José; Birol, Ekin (African Journal of Food, Agriculture, Nutrition and Development, 2017)
Biofortification is regarded as a complement to supplementation, industrial fortification and dietary diversification in the fight against micronutrient deficiencies. It is important therefore to first identify areas where biofortification may have high impact and prioritize these areas for more in-depth analysis. HarvestPlus has developed the Biofortification Prioritization Index (BPI), which ranks countries globally according to their suitability for investment in biofortification interventions. HarvestPlus is also conducting ex ante micronutrient intervention portfolio analyses, designed to simulate the implementation and impact of a biofortification program in countries which have been identified as suitable candidates for investment. Micronutrient intervention portfolio studies offer the ability to distinguish production, consumption and inadequate micronutrient intake at a more disaggregated level and offer a complementary design and planning tool to simulate the implementation of biofortification and examine its potential impact and costeffectiveness among different approaches. In addition, these studies are designed to examine multiple interventions within a country, to better understand biofortification’s role in reducing micronutrient deficiency when considered among a suite of interventions. This case study of Zambia demonstrates how these tools can be used to assess the potential impact of biofortification, quantify its cost-effectiveness and examine how it interacts with and complements other interventions. Given the long-term nature of biofortification as an intervention investment, future analyses should continue to incorporate various scenarios including continued investment in sustainable development and the effects of climate change which are likely to condition the impact of biofortification and other interventions.